Pengembangan Sistem Filsafat Pancasila - Sudarso Sudarso (Jurnal Filsafat "WISDOM", 2006)
Pancasila is a system of philosophy, the relation of eachprinciple is hierarchy-pyramidal. Logical consequence of Pancasilaas a philosophical system, therefore, is give basis for the implementation inIndonesian government practice—economic, culture, law, defend, socialethic, technology, and education system. Pancasila ought to give meaningnot only as “The five principles of ethic”, but naturally, Pancasila is “Thefive principles of Indonesian Nationality”. It is very important tonote that in the nation-state life, Pancasila as national identity mustbe developed in order to make Indonesian people standing parallelwith other peoples in welfare and justice condition. The differenceinterpretation of Pancasila does not make it poor but instead ofmake it powerful as a system of philosophy.